2016
DOI: 10.1007/s12020-016-1166-4
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide improves cardiac function in patients with type 2 diabetes and chronic heart failure

Abstract: These data provide evidence that treatment with liraglutide is associated with improvement of cardiac function and functional capacity in failing post-ischemic type-2 diabetes mellitus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…The newest class of medications, which treat both type 2 diabetes and obesity, is the GLP-1 analogues. Increasing evidence suggests that these medications are efficacious not only at reducing weight, but also at improving the comorbidities of obesity, including cardiovascular disease, non-alcoholic steatohepatitis [35,36] and overall mortality [3739]. Similar results to the most recent study, above, with liraglutide were demonstrated by this study group in the shorter-term.…”
supporting
confidence: 85%
“…The newest class of medications, which treat both type 2 diabetes and obesity, is the GLP-1 analogues. Increasing evidence suggests that these medications are efficacious not only at reducing weight, but also at improving the comorbidities of obesity, including cardiovascular disease, non-alcoholic steatohepatitis [35,36] and overall mortality [3739]. Similar results to the most recent study, above, with liraglutide were demonstrated by this study group in the shorter-term.…”
supporting
confidence: 85%
“…Previous smallsample, retrospective studies showed that GLP-1 was associated with favourable effects that GLP-1 significantly improved LV function, functional status, and the QoL [138]; and that GLP-1 reduced the risk of HHF, all-cause hospitalization, and death in T2DM [139]. Another study involving 32 T2DM patients with a history of CHF provided evidence that treatment with liraglutide is associated with improvements in cardiac function and functional capacity [140]. However, in LEADER, the rate of the primary composite outcome in the time-to-event analysis (the first occurrence of death from cardiovascular causes, nonfatal MI, or nonfatal stroke) among patients with T2DM and high cardiovascular risk was lower with liraglutide than with placebo, whereas the number of HHF was reduced non-significantly in the active arm [141].…”
Section: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 95%
“…Sitagliptin and liraglutide have been shown to improve diastolic function in the short term [11][12][13][14] and diabetes mortality increases with E/e′. 15 This may be the first report of differential effects of GLP-1 analogue and DPP-4 inhibitors on cardiac diastolic function with follow-up as long as 48 months.…”
Section: Discussionmentioning
confidence: 81%